2009
DOI: 10.1111/j.1476-5381.2009.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid receptor antagonists: development strategies and therapeutic applications

Abstract: Identification of the primary products of cyclo-oxygenase (COX)/prostaglandin synthase(s), which occurred between 1958 and 1976, was followed by a classification system for prostanoid receptors (DP, EP1, EP2 . . .) based mainly on the pharmacological actions of natural and synthetic agonists and a few antagonists. The design of potent selective antagonists was rapid for certain prostanoid receptors (EP1, TP), slow for others (FP, IP) and has yet to be achieved in certain cases (EP2). While some antagonists ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
162
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 435 publications
(456 reference statements)
2
162
0
Order By: Relevance
“…2). Second, the ability of taprostene to enhance GRE-dependent transcription in BEAS-2B reporter cells was antagonized in a competitive manner by RO3244794, an IP-receptor-blocking drug, with an affinity (pK b ϭ 9.21) consistent with an interaction at IP-receptors (27,43). Collectively, these results strongly suggest that in BEAS-2B cells, taprostene augments GRE-dependent transcription by an IPreceptor-mediated mechanism.…”
Section: Selection Of Taprostene As An Ip-receptor Agonistmentioning
confidence: 72%
“…2). Second, the ability of taprostene to enhance GRE-dependent transcription in BEAS-2B reporter cells was antagonized in a competitive manner by RO3244794, an IP-receptor-blocking drug, with an affinity (pK b ϭ 9.21) consistent with an interaction at IP-receptors (27,43). Collectively, these results strongly suggest that in BEAS-2B cells, taprostene augments GRE-dependent transcription by an IPreceptor-mediated mechanism.…”
Section: Selection Of Taprostene As An Ip-receptor Agonistmentioning
confidence: 72%
“…[15][16][17] Mizuguchi, et al revealed that myoelectrical activity was suppressed by continuous infusion of ONO-DI-004 into the gastric artery. This demonstrates that EP1 signaling has a crucial role in the suppression of myoelectrical activity of gastric smooth muscles and inhibition of gastric emptying.…”
Section: Synthesized Ep Agonists I) Ep1 Agonistsmentioning
confidence: 99%
“…19) ii) EP2 agonists: ONO-AE1-259, CP-533536, 19(R)-hydroxy PGE 2 , AH13205 and misoprostol are known as major EP2 agonists. 16,17) Among them, ONO-AE1-259 has been widely used to clarify the roles of EP2 ( Figure 1C). This compound reduced the infarct volume correlated with improved neurologic scores in mice.…”
Section: Synthesized Ep Agonists I) Ep1 Agonistsmentioning
confidence: 99%
See 2 more Smart Citations